Meta-Analysis and Systematic Review: Analysis of Antibiotic Residues and Bacteria in Indonesia's Egg and Its Threat to Public Health: A Literature Review - Aulia Umi Rohmatika; Fairuz Haniyah Ramadhani (Journal of Diverse Medical Research : Medicosphere, 2026)
Eggs are the most popular source of protein in Indonesia. The quality of eggs is prone to decline due in management and handling. Eggs can be damaged, one cause of which is microbial growth. Many studies also proved that some eggs sold on the market contain antibiotic residues. The purpose of this study is to determine the presence of antibiotics and bacterial residues on eggs circulating in Indonesia. This study also aims to conduct research on the health risks of eggs containing antibiotic and bacterial residues. This study used meta-analysis and a systematic review. The article search method employs PICO and snowballing techniques across three databases: Google Scholar, ScienceDirect, and PubMed. The articles used are research articles conducted in Indonesia and published between 2012 and 2022. Articles were selected and analyzed as many as 18 articles. This study showed that the findings of bacteria in eggs in Indonesia were OR 0.67 (95% CI 0.52 – 0.88) with a pooled value of OR nial e0.69 = 1.95. Meanwhile, for the OR value of antibiotic residues was 0.28 (95% CI 0.20 – 0.39) with pooled OR e0.28 was 1.32. However, the two results of the study show that there is a bias in the article of the two variables. Consumption of eggs containing antibiotic residues and bacteria can cause various health impacts. In this study, it was found that some eggs in Indonesia contain antibiotic and bacterial residues. Eggs containing antibiotic residues and bacteria can be a threat to public health